EMPOWERING YOUNG LEARNERS IN ENGLISH EDUCATION: POTENTIAL AND LIMITATIONS OF SUNO AI - phalaguna, ida bagus (Yavana Bhasha : Journal of English Language Education, 2024)
Engaging and maintaining young learners’ attention spans with songs has been a common technique in the teaching of English. However, looking for suitable and perfect songs on the internet has always been difficult and takes much time for those teachers who want to include music in their classes. Now, this challenge is made easier by SUNO, a generative AI that creates songs quickly and effectively. Nevertheless, like any other technology, SUNO is not flawless AI. There are some downsides associated with SUNO as well. For example, the quality of the songs depends on the prompt it receives. Moreover, its operation relies on an uninterrupted connection to the internet which might not be available at certain institutions such as rural areas.